Dampak Keamanan Digital Banking terhadap Kualitas Pelayanan - Resi Juariah Susanto (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
This research examines the implications of the rapid development of digital banking technology on user security and analyzes how banking service quality influences the level of security and convenience experienced by customers when using digital banking services. The increasing adoption of digital financial services has created significant opportunities for improving transaction efficiency and accessibility, while also introducing various cybersecurity risks and challenges related to data privacy and consumer protection. From an operational management perspective, service quality is a critical element that must be managed consistently and sustainably to achieve customer satisfaction, strengthen trust, and enhance long-term customer loyalty. This study employs a qualitative literature review approach by collecting, reviewing, and analyzing books, scientific journals, government regulations, and other relevant publications concerning digital banking security and banking service quality. The findings indicate that high-quality banking services supported by robust security systems, effective risk management, and reliable digital infrastructure contribute significantly to improving customer confidence and reducing perceived security risks. Therefore, banks should continuously strengthen cybersecurity measures, enhance service quality, and implement customer-oriented digital innovations to ensure secure, efficient, and reliable digital banking services. The results of this study are expected to enrich the literature on digital banking and provide practical recommendations for banking institutions, policymakers, and future researchers.